MODEL KOLABORATIF UNTUK INTEGRASI KAJIAN LINGKUNGAN HIDUP STRATEGIS DALAM PERENCANAAN PEMBANGUNAN - Reinal Putalan; Rostiati Rahmatu; Muhammad Nur Sangaji (Politeknik Kebangsaan, 2025)
This community engagement initiative aims to develop a collaborative model for facilitating the formulation of Strategic Environmental Assessment (SEA) as part of medium-term development planning. The approach combines participatory methods, document analysis, and multi-stakeholder consultation forums to ensure the integration of sustainable development principles into local policy and program frameworks. The facilitation process includes strategic issue mapping, gap analysis of Sustainable Development Goals (SDGs) indicators, and the formulation of data-driven alternative development scenarios. The role of academic facilitators has proven vital in enabling cross-sectoral dialogue, improving planning literacy, and strengthening institutional capacity for evidence-based decision-making. This article reflects on the application of a collaborative methodological approach to enhance inclusive and sustainable governance in local development contexts..